Analysis of occurrence patterns and biological factors of cetaceans based on long‐term and fine‐scale data from platforms of opportunity: Madeira Island as a case study. (17th May 2018) - Alves, Filipe; Ferreira, Rita; Fernandes, Miguel; Halicka, Zofia; Dias, Luís; Dinis, Ana
Abstract: Management and conservation issues are addressed through the identification of areas of particular importance, which requires the acquisition of baseline information on species distribution and dynamics. These types of data are particularly difficult to obtain at high resolution for large marine vertebrates like cetaceans, given that dedicated surveys are complex and logistically expensive. This study uses daily presence–absence sighting data of cetaceans collected year‐round from whale‐watching boats to support the theory that fine‐scale data obtained from platforms of opportunity can provide valuable information on species occurrence and group dynamics. Data from 7, 551 (daily) sightings comprising 22 species were collected from 3, 527 surveyed days over 11 years (mean of 321 days per year, SD = 17) in the pelagic environment of Madeira Island. Cetaceans were observed on 92% of the surveyed days, and a mean of 15.4 ( SD = 1.5), 8.2 ( SD = 2.0) and 2.1 ( SD = 1.2) species were recorded per year, month, and day, respectively. There were significant differences in the number of species per month ( p < .001), with the highest diversity recorded in June. At least nine species, comprising 96% of all sightings, were found to use the Madeiran waters on a regular basis, such as the Atlantic spotted dolphin ( Stenella frontalis ), the short‐beaked common dolphin ( Delphinus delphis ), the bottlenose dolphin ( Tursiops truncatus ), and others featured in the Red List of the International Union for Conservation of Nature as Endangered, Vulnerable, and Data Deficient. In addition, 10 species were found to use the Madeiran waters for travelling, feeding, resting, socializing and calving, which suggests that the southern and southeastern waters of Madeira Island constitute an area of interest for cetaceans. This study characterizes the cetaceans' community structure (occurrence, aggregation sizes, behaviours, proportion of calves, and inter‐specific relationships) of a poorly studied region, providing important information for managers. Finally, the advantages and limitations of using fine‐scale data from a type of platform of opportunity that is increasing along coastlines globally are discussed.